Excessive somnolence - Tavares, Stella (1996)
Excessive somnolence can be quite a incapacitating manifestation, and is frequently neglected by physicians and patients. This article reviews the determinant factors, the evaluation and quantification of diurnal somnolence, and the description and treatment of the main causes of excessive somnolence.